(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
This study includes the evaluation of the problem of seawater intrusion in Al-Bassa area in 2014 through chemical monitoring of a group of sampling wells, under certain condition that were subjected to the area during the research, representing by rainfall precipitation in the study area was only 500 mm/ year, as a result in the suspension of irrigation from 16 October lake and reuse of many abandoned pumping wells. This study founds an increasing in the salinity values in the Al- Bassa coastal area of summer in 2014, ranging between(665.6-6432mg/l)after increasing daily pumping rates, in addition to the increasing of chloride and sodium concentrations in most of sampling wells water in conjunction with high salinity levels. In the fall, the salinity values ​​ranged between 490-950 mg / l. The geochemistry of Na/Cl indicates values ​​ less than 0.84 in most water samples during the summer, while in autumn this percentage was higher than 0.84 in most samples ,to be an indicator for marine water.